2013
DOI: 10.5935/abc.2013s003
|View full text |Cite
|
Sign up to set email alerts
|

I Diretriz sobre o consumo de Gorduras e Saúde Cardiovascular

Abstract: I Diretriz sobre o consumo de Gorduras e Saúde Cardiovascular Definição do grau dos níveis de evidência Recomendações Classe I: Condições para as quais há evidências conclusivas e, na sua falta, consenso geral de que o procedimento é seguro útil/eficaz. Classe II: Condições para as quais há evidências conflitantes e/ou divergência de opinião sobre segurança e utilidade/ eficácia do procedimento. Classe IIa: Peso ou evidência/opinião a favor do procedimento. A maioria aprova. Classe IIb: Segurança e utilidade/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
2
148

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(283 citation statements)
references
References 233 publications
(313 reference statements)
4
129
2
148
Order By: Relevance
“…De maneira geral, sob o ponto de vista de saúde, é desejável uma carne com menores teores de ácidos graxos saturados. Segundo Santos et al (29) , a gordura saturada (C12:0, C14:0 e C16:0), quando consumida, eleva a concentração plasmática de colesterol, aumentando o risco de doenças cardiovasculares.…”
Section: Resultsunclassified
“…De maneira geral, sob o ponto de vista de saúde, é desejável uma carne com menores teores de ácidos graxos saturados. Segundo Santos et al (29) , a gordura saturada (C12:0, C14:0 e C16:0), quando consumida, eleva a concentração plasmática de colesterol, aumentando o risco de doenças cardiovasculares.…”
Section: Resultsunclassified
“…The high intake of red meat by the population of São Paulo results mainly in high intake of saturated fat, and this type of fat is an important factor in the development of cardiovascular diseases and other diseases 20 . The high intake of meats, especially processed meats, may also contribute to the high intake of sodium (low score) by people with high protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of high fat level, especially saturated fat, is associated with the increased risk of dementia, diabetes, and heart disease, which affect mainly the elderly population 10 . The I Brazilian Guideline about the Intake of Fats and Heart Health reinforces the importance of reducing saturated fatty acids in the diet 26 , and it was observed that, regardless of gender, situation of the household and macro-region, the intake of saturated fat was close to or higher than the recommended limit of 10% of the total energy consumed.…”
Section: Discussionmentioning
confidence: 99%